'So Numerous, So Cheap, and So Changing': G. K. Chesterton and the Speed of Modernity. (April 2015) - Mitchell, Philip Irving
Abstract: This article explores the trust in existence that allowed G. K. Chesterton in his occasional writing on cinema to bring together film with sculpture, automobiles, and the meaning of place and history. At the heart of his diverse concerns was wonder as a basic human need and as a basic source of engagement with the world. A sense of amateur play and of ontological dependence, he held, enables the reception of the gifts of the world, as does a slow, continuous attention to life and history. Against these, Chesterton opposed progressivism and Futurism as ideologies that flatten reality through grasping for control and for power; Rather than the experience of speed itself, modernity may contain ideological commitments that dampen, or even erase, joy. Loyalty to the world and its most fundamental givenness, for Chesterton, included a love of the past that opens us to the complexity and abundance of human life, and in turn orients us to a responsible posture before the present. To attend to the good world we must open ourselves repeatedly to its riches, well-aware that it is not dependent upon us.